Effect of Fuel Additives on the Performance and Emissions of an Internal Combustion Engine - Mohamed Khatab, Marwan (Universiti Teknologi Petronas, 2011)
Internal combustion engines fuel additives producers claim that with the addition of some additives to diesel fuel, an engine can function better in terms of performance and efficiency and decrease the emissions due to the combustion process as well. The diesel engine thermal efficiency ranges from about 35 to 40 percent. The diesel fuel price in Malaysia is about RM 1.80 per liter. The emissions due to the combustion of diesel fuel include mostly COx and NOx emissions. A study must be carried out in order to validate the claims of the fuel additives producers and find out the effect of the additives on the performance and the emissions of the diesel engine. The objective of this project is to carry out the experiment needed to validate the claims throughout running an engine · using an additive free diesel fuel and an additive on diesel fuel. This experiment is conducted through using two fuel additives. After testing the fuel with the additives and without the additives the results of the experiment are tabulated, comparing torque, power, specific fuel consumption and exhaust temperature with respect to the engine's speed. A single cylinder two strokes diesel engine is used in this experiment with and without the additives. The parameters of interest in this study would be (Torque, Fuel consumption, power and exhaust temperature) According to recent researches made by few researchers some additives validated the claims of the fuel additives producers. Some of these research results is included with further details in this report.